The effect of global financial markets and local shocks on Turkey airlines market: New evidence from structural break cointegration and causality tests - Hasraddin Guliyev (Research in Globalization, 2022)
This study examines the relationship between Turkey's airline markets, which responded to local economic shocks, and the USA and Europe airlines market using daily closing stock price data from January 2016 to June 2022. All the variables are non-stationary at level but stationary at first difference. The long-run relationship among the variables is found by employing Maki's (2012) cointegration test considering multiple unknown structural breaks. In addition, the Granger causality analysis results of markets support the correlation of stock prices. The relationship between the global airlines market and Turkey's airlines market is analyzed with different regimes supporting structural breaks. This methodological framework may be considered a significant contribution to financial research.
Keywords: G15; C22; C58; 330; Airlines industry; Cointegration analysis; Financial markets; Stock prices